2016
DOI: 10.14260/jemds/2016/988
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Parasitic and Bacterial Infection Among Food Handlers in a Metropolitan Tertiary Care Hospital

Abstract: Food borne diseases are a global public health burden. Food handlers play a major role in the transmission of foodborne diseases. This study was aimed at investigating the presence of intestinal parasites, S. typhi carrier rate and associated risk factors among food handlers in a metropolitan city. MATERIALS AND METHODSA cross-sectional survey was conducted among 200 food handlers working in different food service establishments. A pre-tested structured questionnaire was used to collect data on age, sex, years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…were found in two samples (2.5%), which is consistent with other studies that found no enterobacterial infection from stool cultures among food handlers in Kanchanaburi province of Thailand [22], in a tertiary care hospital of India [25], or the Dead Sea area of Jordan [16]. Enterobacteria in stool cultures have been reported from other areas: Shigella boydii was found 0.9% in northern Iran and 1.3% in the Omdurman area of Sudan [23,24], Samonella typhi was found in 1% of samples collected in a tertiary care hospital of Mumbai and 1.3% in the Omdurman area of Sudan [15,24], and Salmonella was isolated from 3.5% of samples in Addis Ababa, Ethiopia [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…were found in two samples (2.5%), which is consistent with other studies that found no enterobacterial infection from stool cultures among food handlers in Kanchanaburi province of Thailand [22], in a tertiary care hospital of India [25], or the Dead Sea area of Jordan [16]. Enterobacteria in stool cultures have been reported from other areas: Shigella boydii was found 0.9% in northern Iran and 1.3% in the Omdurman area of Sudan [23,24], Samonella typhi was found in 1% of samples collected in a tertiary care hospital of Mumbai and 1.3% in the Omdurman area of Sudan [15,24], and Salmonella was isolated from 3.5% of samples in Addis Ababa, Ethiopia [21].…”
Section: Discussionmentioning
confidence: 99%
“…In separate studies, in Ethiopia, 14.8% [8], 41.1%, and 44.1% using direct mount and concentration technique of food handlers were infected; [9,10], in Iran, 3.7% (wet mount method), 9% (wet mount, concentration technique, trichrome staining), 10.4% (wet mount, concentration technique; and 34.9% (wet mount, concentration technique, Ziehl-Neelsen and trichrome staining) of handlers infected [11][12][13][14]. Infection rates using direct mount and concentration technique were 15.5% in Mumbai [15] 3.7% in Jordan [16]. Using Lutz, modified Ritchie, and Ziehl-Neelsen techniques, it was 38.2% in Brazil [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food handlers who work in the food service sector with poor personal hygiene are the potential source of pathogenic organism infection (Acikel et al, 2008;Mukhopadhyay et al, 2016;Anjum et al, 2017;Gemeda et al, 2018). The food contamination occurs during food chain process including preparation, production, processing, and the food distribution (Permenkes RI, 2011; Anuradha and Dandekar, 2014; Mukhopadhyay et al, 2016 handlers depends on their health status, personal hygiene, knowledge, and the hygiene practice (Esparar et al, 2010;Dahiru et al, 2016). Foodborne disease is defined as illness resulting from the consumption of contaminated food; food can be contaminated with microbial pathogens or a toxic substance (Unicomb, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The food handlers in Hospital with the bad personal hygiene could be a potential source of infection of a pathogenic organism [1][2][3][4]. The contaminated-food could occur at any point during the bacterial journey through production, processing, distribution, and preparation [2] [5][6]. The risk of food contamination depends on the health status of food handlers, personal hygiene, and knowledge, and practice of food hygiene [7][8].…”
Section: Introductionmentioning
confidence: 99%